Survey on Handwritten Digit Recognition using Machine Learning - Kumar, Narender; Beniwal, Himanshu (International Journal of Computer Sciences and Engineering, 2025)
Machine learning and deep learning plays an important role in computer technology and artificial intelligence. With the use of deep learning and machine learning, human effort can be reduce in recognizing, learning, predictions and many more areas. This paper presents recognizing the handwritten digits (0 to 9) from the famous MNIST dataset, comparing classifiers like KNN, PSVM, NN and convolution neural network on basis of performance, accuracy, time, sensitivity, positive productivity, and specificity with using different parameters with the classifiers